Clinical and Financial Implications of Medicine Consumption Patterns at a Leading Referral Hospital in Kenya to Guide Future Planning of Care - Kivoto, Patrick M.; Mulaku, Mercy; Ouma, Charles; Ferrario, Alessandra; Kurdi, Amanj; Godman, Brian; Oluka, Margaret (Frontiers in Pharmacology, 2018)
Background: Medicines can constitute up to 70% of total health care budgets in developing countries as well as considerable expenditure in hospitals. Inventory management techniques can assist with managing resources efficiently. In Kenyatta National Hospital (KNH), a leading hospital in Kenya, over 30% of expenditure is currently allocated to medicines, and this needs to be optimally managed. Objective: To investigate drug consumption patterns, their costs and morbidity patterns at KNH in recent years. Methodology: Cross-sectional retrospective record review. Inventory control techniques, ABC (Always, Better, and Control), VEN (Vital, Essential, and Non-essential) and ABC-VEN matrix analyses were used to study drug expenditure patterns. Morbidity data was extracted from the Medical Records. Results: Out of an average of 811 medicine types procured annually (ATC 5), 80% were formulary drugs and 20% were non-formulary. Class A medicines constituted 13.2–14.2% of different medicines procured each year but accounted for an average of 80% of total annual drug expenditure. Class B medicines constituted 15.9–17% of all the drugs procured yearly but accounted for 15% of the annual expenditure, whilst Class C medicines constituted 70% of total medicines procured but only 5% of the total expenditure. Vital and Essential medicines consumed the highest percentage of drug expenditure. ABC-VEN categorization showed that an average of 31% of medicine types consumed an average of 85% of total drug expenditure. Therapeutic category and Morbidity patterns analysis showed a mismatch between drug expenditure and morbidity patterns in over 85% of the categories. Conclusion: Class A medicines are few but consume the largest proportion of hospital drug expenditure. Vital and essential items account for the highest drug expenditure, and need to be carefully managed. ABC-VEN categorization identified medicines where major savings could potentially be made helped by Therapeutic category and Morbidity pattern analysis. There was a high percentage of non-formulary items, which needs to be addressed. Inventory control techniques should be applied routinely to optimize medicine use within available budgets especially in low and middle income countries.